Exercises for wrist flexibility, arm power, concentration and shooting results on petanque - Irhas Syahwira; Said Junaidi; Taufiq Hidayah; Sri Sumartiningsih; Setya Rahayiu (STKIP Muhammadiyah Kuningan, 2022)
The aims of this study were: 1) To analyze the effect of wrist flexibility exercise on shooting results; 2) To analyze the impact of arm power training on shooting results; 3) To investigate the effect of concentration training on shooting results; 4) To examine the impact of wrist flexibility exercise, arm power and exercise. Concentration on the results of shooting petanque. This study uses a pre-experimental method with the